Kompetensi Mahasiswa Keperawatan Tingkat Dua dalam Pelaksanaan Keterampilan Praktik Klinis - Naibaho, Kayla Debrisya; Hutapea, Lyna M. N. (Journal of Telenursing (JOTING), 2024)
This study aims to determine the competency abilities of Level 2 nursing students in clinical practice in private hospitals. The method used is univariate descriptive analysis. The research results show five categories of skills: highly skilled, skilled, moderately skilled, less skilled, and not skilled. This data shows that the average percentage of level 2 nursing students carrying out clinical practice competencies in hospitals is in the highly skilled, skilled, and quite skilled competency categories. Level 2 nursing students have pretty good skill competencies in carrying out clinical practice competencies in hospitals, with a highly skilled percentage of 12 people (26.9%), skilled as many as 14 people (31.1%), quite skilled as many as nine people (21 .0%), less skilled as many as four people (10.1%), unskilled as many as five people (10.9%). In conclusion, second-level nursing students were able to carry out 32 assessment items on the achievement of clinical practice skills competency from the Child, KMB, and Maternity courses. Keywords: Skills, Competencies, Clinical Practice